Exploring the role of traditional food in developing tourism in Kazakhstan - Batyrbek, Ayazhan; Chisbiyah, Lismi Animatul (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
This article examines how Kazakhstan can enhance its tourism industry by leveraging its rich traditional food heritage. Gastronomic tourism, a rapidly growing sector focused on immersive culinary experiences, allows travelers to connect deeply with local cultures through food. Positioned at the crossroads of Europe and Asia, Kazakhstan offers a unique culinary landscape shaped by its nomadic traditions, Silk Road history, and diverse ethnic influences. Traditional dishes like beshbarmak, kazy, and baursak provide authentic experiences that showcase the nation’s heritage, while urban centers such as Almaty and Nur-Sultan feature a modern fusion of culinary techniques, adding a dynamic layer to Kazakhstan’s food scene. The article highlights the role of traditional food in driving tourism development, with efforts from the government and private sector to promote Kazakhstan as a culinary destination. By focusing on traditional food as a key attraction, Kazakhstan holds strong potential to enrich its tourism offerings and appeal to an international audience seeking culturally rooted travel experiences. This study employs an applied qualitative research method that integrates a comprehensive literature review, thematic analysis, and comparative analysis to explore the potential of traditional Kazakh cuisine in enhancing tourism development. The findings reveal that Kazakhstan’s unique food practices ranging from innovative methods such as drying, fermenting, and smoking to the fusion of multicultural dish influences offer significant opportunities for immersive gastronomic tourism experiences. These insights suggest that by strategically promoting its traditional cuisine through culinary tours, food festivals, and interactive cooking demonstrations, Kazakhstan can elevate its profile as a distinct culinary destination, thereby enhancing tourist experiences and supporting sustainable economic growth.